Association of dietary diversity changes and mortality among older people: A prospective cohort study. Issue 5 (May 2021) - Liu, Dan; Zhang, Xi-Ru; Li, Zhi-Hao; Zhang, Yu-Jie; Lv, Yue-Bin; Wang, Zheng-He; Shen, Dong; Chen, Pei-Liang; Zhong, Wen-Fang; Huang, Qing-Mei; Wang, Jia-Hui; Zhang, Wen-Ting; et al.
Summary: Background & aims: The association between dietary diversity (DD) changes and mortality remains unclear. We aimed to investigate the association between DD changes and all-cause mortality among older people. Methods: A total of 17, 959 participants with a mean age of 84.8 years old were enrolled at baseline. Food groups were collected at baseline and follow-up using simplified food frequency questionnaire (FFQ), and then overall, plant-based and animal-based dietary diversity score (DDS) were calculated. DDS changes were calculated using DDS at baseline and the first follow-up. The association between three DDS changes (overall, plant-based and animal-based DDS) and subsequent all-cause mortality were evaluated. Nonparametrically restricted cubic splines and a multivariable-adjusted Cox proportional hazards model were used to estimate HRs and 95% CIs. Results: We documented 12, 974 deaths over a 129, 590 person-years of follow up. Compared with high-to-high DDS pattern, participants with lower overall DDS patterns had increased mortality risk with HRs (95%CI) of 1.39 (1.29–1.49), 1.53 (1.37–1.70), 1.38 (1.18–1.60) and 1.55 (1.31–1.83) for medium-to-medium, low-to-low, low-to-high and high-to-low patterns, respectively. And compared with high-to-high DDS pattern, the estimates were 1.34 (1.23–1.46), 1.49 (1.35–1.65), 1.43 (1.23–1.67) and 1.62 (1.40–1.88) for plant-based DDS, and 1.23 (1.15–1.31), 1.29 (1.20–1.40), 1.24 (1.12–1.37) and 1.28 (1.15–1.44) for animal-based DDS for medium-to-medium, low-to-low, low-to-high and high-to-low patterns, respectively. There was a U-shaped association between DDS change scores and mortality, and compared with participants with whose DDS remained stable, those with extreme declines and extreme improvements had higher risks of mortality with HRs (95% CI) of 1.15 (1.09–1.22) and 1.11 (1.04–1.17). Conclusions: Maintaining a lower DDS, extreme declines and extreme improvements in DDS were all associated with an increased risk of all-cause mortality.